Gender Differences in the Directness of Request Strategies in the Movies Ocean’s Eight and Ocean’s Eleven - Aracelly, Aisya; Sutrisno, Adi (Lexicon, 2024)
This research examined the level of directness of request strategies found in the movies Ocean’s Eight and Ocean’s Eleven. The topic of request strategies itself is important to study in a way that even though all people use it in their daily lives, the act has been used differently by different people. This paper also aimed to see whether there are differences in request strategies made by male and female characters in terms of politeness strategies. The data used in this study are the utterances spoken by the characters that contain request strategies. The data then were analyzed using the theory proposed by Blum-Kulka and Olshtain (1984), followed by the classification of politeness strategies using the combined theory from Holmes (1995) and Brown and Levinson (1987). The result shows that the male characters used direct strategy (Mood Derivable) the most with 57 occurrences (58%). Meanwhile the female characters preferred using conventionally indirect strategy (Query Preparatory) the most with 18 occurrences (33%). Furthermore, this research found that male characters tended to use Bald-On-Record strategy while requesting (71%) and they also found using Referential Tags (2%) as Holmes (1995) stated that men prefer using the referential tag to check their statement’s accuracy. The strategy that was mostly used by female characters was Bald-On-Record as well (35%).  However, this strategy is balanced out with other strategies which were Affective Tags (31%). Affective Tags are preferred by women to soften their request or potential threat (Holmes, 1995).